Biochemical composition and germination capacity of Ligustrum lucidum ait. seeds in the process of biological invasion - doi: 10.4025/actascibiolsci.v34i3.10641 (Acta Scientiarum. Biological Sciences, 2012)
Ligustrum lucidum ait. is an exotic species and In the present study, contents of sugars, proteins, and germination were evaluated in seeds removed from not abscisic and abscisic fruits. The seeds were stored or not  under shadow or sun. The higher contents of total and reducing sugars were observed in seeds removed from not abscisic fruit while the period of storage resulted in the loss of these compounds. The same result was observed in the content of total sugars of seeds from abscisic fruits. The content of reducing sugars in seeds from abscisic fruits and submitted to storage had its content increased. The contents of total proteins in seeds from abscisic and not abscisic submitted to shadow or sun were not significantly different, but the results suggested an increase in protein synthesis during the storage period, differently from those seeds that were not submitted to storage. When seeds from abscisic and not abscisic fruits were evaluated immediately after harvest, they presented greater percentages of germination, while after 28 days, seeds submitted to the storage treatments showed lower values. The invasive potential of L. lucidum seems to be more associated to the number of seeds produced, than to their germination potential.